A Review of Perovskites Solar Cell Stability. (12th February 2019) - Wang, Rui; Mujahid, Muhammad; Duan, Yu; Wang, Zhao‐Kui; Xue, Jingjing; Yang, Yang
Abstract: In this review, the factors influencing the power conversion efficiency (PCE) of perovskite solar cells (PSCs) is emphasized. The PCE of PSCs has remarkably increased from 3.8% to 23.7%, but on the other hand, poor stability is one of the main facets that creates a huge barrier in the commercialization of PSCs. Herein, a concise overview of the current efforts to enhance the stability of PSCs is provided; moreover, the degradation causes and mechanisms are summarized. The strategies to improve device stability are portrayed in terms of structural effects, a photoactive layer, hole‐ and electron‐transporting layers, electrode materials, and device encapsulation. Last but not least, the economic feasibility of PSCs is also vividly discussed. Abstract : In parallel with the tremendous progress in the efficiency of perovskite solar cells, research on the issue of instability has attracted enormous attention . In this review, the strategies to enhance the stability from the perspectives of the device structure, the photoactive layer, hole‐ and electron‐transporting layers, electrode materials, and device encapsulation are portrayed.